Lifestyles during The Roaring 20s of America in F. Scott Fitzgerald’s The Great Gatsby - Busyeiri, Muhammad Latif; Dinanti, Nasyafka (Lililacs Journal, 2021)
Literature is the result of human interaction and culture in which they reflect or imitate the condition of the era they were written in. Due to this reason, some literature is able to function as a way for modern-day readers to have an understanding on how life was like in the past. F. Scott Fitzgerald’s The Great Gatsby is one such novel that contains similar condition during the roaring 20s of America. The novel contains different lifestyles of the American people during the time and revealed the harsh reality of those who were idolizing The American Dream. Using sociological approach, this study aims to learn about the social condition during the roaring 20s of America. Lifestyles during the roaring 20s of America in F. Scott Fitzgerald’s The Great Gatsby is chosen as the title of the study to find out the lifestyle that existed during the roaring 20s of America as reflected in The Great Gatsby. The result of the study shows that different lifestyles that existed during the roaring 20s of America as shown in The Great Gatsby are wealthy lifestyle, modest lifestyle criminal lifestyle, hedonistic lifestyle, impoverished lifestyle. And surrounding factors such as different social class and social gap that existed during the time.